Dual‐band metal skin UHF RFID tag antenna. Issue 14 (1st July 2013) - Du, G.H.; Tang, T.; Deng, Y.
Abstract : A novel dual‐band metal skin UHF radio‐frequency identification tag antenna for 866/915 MHz applications is proposed, which is suitable for attaching to metallic objects. To achieve long read ranges within dual band on an ultra‐thin substrate, the antenna is designed with two patch arrays printed on a flexible substrate polypropylene for low‐cost production. The prototype antenna is fabricated and tested with the commercial tag chip by dual‐port connection. The experiment results show that it has similar radiation patterns for the dual band and the read ranges are 3.5 and 3.6 m for 866 and 915 MHz, respectively, when it is mounted on a metal plate.